Transformasional Leadership and Organizational Commitment: The Mediating Role Of Job Statisfaction - Putera, Rahmad Ridho Arif; Trinanda, Okki (Universitas Negeri Padang, 2023)
This study analyzes (1) the relationship between transformational leadership and organizational commitment; (2) the relationship between transformational leadership and job satisfaction; (3) the relationship between job satisfaction and organizational commitment; and(4) the relationship between transformational leadership and organizational commitment through the mediating role of job satisfaction. This investigation focused on the causes as 61 teachers at SMAN 1 Bukittinggi constituted the entire study population. The sampling method used in this study is using total sampling, where the entire population is sampled. This research uses software called SmartPLS4 used for the analysis method. Data analysis in this study revealed that: (1) Transformational leadership has a positive and significant effect on organizational commitment in teachers of SMAN 1 Bukittinggi.; (2) Transformational leadership has a positive and significant effect on job satisfaction in teachers of SMAN 1 Bukittinggi.; (3) Job satisfaction has a positive and significant effect on organizational commitment in teachers of SMAN 1 Bukittinggi.; (4) Transformational leadership has a positive and significant effect on organizational commitment of teachers at SMAN 1 Bukittinggi through job satisfaction.